Generation Z Behavior: The Impact of Hedonic Shopping Motivation and Fear of Missing Out (FoMO) on Impulse Buying - Arianti Waruwu; Edwin Zusrony (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study explores how Hedonic Shopping Motivation and FoMO drive Impulse Buying in Gen Z. To achieve this, a quantitative approach was applied. Primary data was collected through a structured online questionnaire using a 5-point Likert scale. Participants were defined as all users aged 18-25 from Semarang Regency registered on Tokopedia or Shopee. A non-random purposive sampling technique determined eligibility, leading to a final participant pool of 60 respondents. Data were analyzed using multiple linear regression and processed with SmartPLS version 4.1.1.2. The findings revealed that Hedonic Shopping Motivation did not show a significant and positive effect on Impulse Buying, while FoMO exerted a meaningful influence on the study's impulse buying metrics. However, collectively, Hedonic Motivation and FoMO exerted a positive and significant influence when considered together or simultaneously. The results offer actionable insights for Gen Z consumers by clarifying how shopping enjoyment and, to a lesser extent, fear of missing out collectively shape impulse buying behavior across e-commerce platforms, effectively identifying the key drivers influencing the endogenous constructs evaluated.